Parental stress and depression symptoms among B40 wives of drug addicts in Malaysia: resilience as a mediator - Ahmad Shahril, Nurul Saidatus Shaja'ah; Arshat, Zarinah; Adnan, Haikal Anuar (F1000 Research, 2022)
Background: The prevalence of depression is higher among women in the general population. While previous studies have contributed to demonstrating a higher risk of depression among women, there is a scarcity of studies on depression issues among women who experienced life as a spouse to drug addicts. Therefore, the present study aimed to investigate the association between parental stress faced in raising children and depression. Moreover, the study intended to examine the impact of parental stress on depression as mediated by resilience. Methods: Using the purposive sampling method, a total of 132 B40 wives of drug addicts were chosen to participate in this study. Data were collected from six states in Malaysia using a structured questionnaire consisting of the Parental Stress Scale (PSS), Brief Resilience Scale (BRS), and Zung’s Self-Rating Depression Scale (SDS). SmartPLS software version 3.3.7 was used to analyze the data collected. Results: Path analysis revealed that parental stress was significantly associated with depression through resilience. Specifically, the indirect effect highlighted that resilience was a partial mediator in the association between parental stress and depression. Nevertheless, it is also shown that even after accounting for the mediating role of resilience, parental stress still has a positive impact on depression. Conclusions: The present study proffers additional strategies to drug addicts’ wives, advocates, academicians, practitioners, and policymakers to approach depression issues in this community for better well-being.